Current Ratio, Debt to Equity Ratio, dan Return on Asset terhadap Return Saham - Hasanudin Hasanudin (IPM2KPE, 2022)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, and Return On Assets on Stock Returns in telecommunication services sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. This research method is descriptive quantitative. This data source uses secondary data in the form of financial statements from each of the telecommunications services sub-sector companies from 2017-2021. The method used in this study is multiple linear regression using the EVIEWS 9 application. The results show, Current Ratio (CR) has a positive and insignificant effect on stock returns, Debt to Equity Ratio (DER) has a negative and insignificant effect on stock returns, and Return on Assets (ROA) has a negative and insignificant effect on Stock Return. Conclusions, a) the size of the Current Ratio does not necessarily produce a high return, b) the company experiences a decrease in the value of the company if there is an increase in debt in the company; c) changes in the value of return on assets will give a negative contribution to stock returns. However, if ROA increases, the company will get a low share return contribution or vice versa, a smaller change in the value of return on assets will have an impact on higher stock returns. Keywords: Current Ratio, Debt to Equity Ratio, Return on Assets, Stock Return